2009
DOI: 10.1038/ejhg.2009.97
|View full text |Cite
|
Sign up to set email alerts
|

Comparing population structure as inferred from genealogical versus genetic information

Abstract: Algorithms for inferring population structure from genetic data (ie, population assignment methods) have shown to effectively recognize genetic clusters in human populations. However, their performance in identifying groups of genealogically related individuals, especially in scanty-differentiated populations, has not been tested empirically thus far. For this study, we had access to both genealogical and genetic data from two closely related, isolated villages in southern Italy. We found that nearly all livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…One study revealed strong genetic inbreeding in two isolated villages in Italy six km apart from each other. Extensive genealogical data of all participants from those villages confirmed the observed inbreeding patterns based on full genome data and could give more insights in the effect of inbreeding on the genome (Colonna et al, 2009). Another genomic study in Quebec (Canada) by Roy- showed significant population structure that corroborated the genealogical analysis that was performed previously (Gagnon and Heyer, 2001;Bherer et al, 2011).…”
supporting
confidence: 54%
“…One study revealed strong genetic inbreeding in two isolated villages in Italy six km apart from each other. Extensive genealogical data of all participants from those villages confirmed the observed inbreeding patterns based on full genome data and could give more insights in the effect of inbreeding on the genome (Colonna et al, 2009). Another genomic study in Quebec (Canada) by Roy- showed significant population structure that corroborated the genealogical analysis that was performed previously (Gagnon and Heyer, 2001;Bherer et al, 2011).…”
supporting
confidence: 54%
“…Despite clustering analysis of the villages showing no significant stratification (P-value 40.05 for both first and second principal components, Supplementary Figure 8), F ST values indicate some extent of structuring, which has already been observed in isolates, 43,44 even for populations with recent shared genealogy. 45 We speculate that the slight observed stratification can be related to the high proportion of marriages occurring between inhabitants of the same village, as demonstrated by analysis of marriage acts and surnames (data not shown). Further, we observe a more rapid decay of LD in the valley with respect to villages and opposite trend of LD-based estimates of nN e consistently with metapopulation dynamics.…”
Section: Population Clusteringmentioning
confidence: 84%
“…[10][11][12] Evidence of population structure accumulates at the scale of European countries [13][14][15][16][17][18] and even at a finer scale. 19,20 Fine-scale genetic structure can result from different processes including founder effect, endogamy, historical migration, cultural barriers to gene flow or selection processes. 11,21,22 Our study focuses on genetic variation in Western France as defined by Historical Geography literature.…”
Section: Introductionmentioning
confidence: 99%